If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + 2d = 8 Solving 3c + 2d = 8 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2d' to each side of the equation. 3c + 2d + -2d = 8 + -2d Combine like terms: 2d + -2d = 0 3c + 0 = 8 + -2d 3c = 8 + -2d Divide each side by '3'. c = 2.666666667 + -0.6666666667d Simplifying c = 2.666666667 + -0.6666666667d
| 2y-2=3 | | 3x-2+5=2(5x-4) | | z^3-j=0 | | 7.50x+8y=93.50 | | 4x=0.9 | | 6a-4b-2a+24b= | | 6-2(x+8)=6x-26 | | 5(2-7)-y=2(y+1) | | 45+5x=5 | | X+(x-4)+2(x-4)=24 | | y+2.5=.5 | | 5=5x+45 | | 4z+9=-9 | | 7z+8=64 | | 6+18=-y+11 | | 30=q-31 | | 1z+8=13 | | W-7=19 | | 1+1(4X*5)= | | 2=n-96 | | 1y+8=13 | | T-38=53 | | 4f=72 | | 4=p-4 | | 2z=4.8 | | 2x-9=3(x-9) | | 10x-3+77= | | -9t/14-t/7=1 | | 17.78=g+8.13 | | 9=3/4e;e=12 | | x^3=-27m^18n^12 | | C/3=4.2 |